Business Models in the Area of Logistics In Search of Hidden Champions, their Business Principles and Common Industry Misperceptions - Neubauer, Regina M.; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
The significance of managing end-to-end supply chains from one hand has been the subject of discussion for over ten years. Regina M. Neubauer provides an answer on how such a scenario might work by studying small- and medium-sized enterprises in the European logistics industry based on her Business Model Performance Scoring Framework. She proves that small- and medium-sized enterprises in logistics are sustainable, i.e. she identifies Hidden Champions that are successful partners in a collaborative business model by offering individualized solutions.
Keywords: Economics; Economics/Management Science; Production/Logistics/Supply Chain Management